THE SIMULATION OF VIRTUE SOCIALLY ACCEPTED COMPENSATIONS TO HIDE EMPTINESS - Godínez, Héctor Sevilla (2019)
The intention of this article is to explain some of the conditions that cause the experience of emptiness to be harmful. It is noted that the experience of feeling empty, although it brings with it an opportunity for development, increased awareness or fullness, is not always the case. Therefore, the text has the pretension to show the reasons why emptiness is not represented as an opportunity for growth or something worthy of being valued. Different simulations of virtue that are usually accepted are addressed separately, such as the need for perfection, messianic attitudes, the accumulation of compensatory knowledge, the excessive af rmation of personal virtue and the masks that distort identity to hide the emptiness.